Integrated IBL Methods in L-STEAM and SEL to Support Deep Learning: Stimulating Children’s Executive Functions - Erie Siti Syarah; Siti Aisyah; Muktia Pramitasari; Murni Murni; Waliatun Isnaini; Christania Anthonny; Sharfina Nur Utama Justicia; Ayu Riagandi (Universitas Pendidikan Ganesha, 2026)
Learning that supports young children’s executive functions is essential to building foundational higher-order thinking skills. However, an integrated approach combining Inquiry-Based Learning (IBL), L-STEAM, and Social Emotional Learning (SEL) has rarely been implemented simultaneously in early childhood education. This study aims to examine the effectiveness of the IBL approach integrated with L-STEAM and SEL in enhancing children’s executive functions. A mixed-methods design with an explanatory sequential model was employed. The participants included 30 children aged 5–6 years, 4 teachers, and 30 parents from a kindergarten in Indonesia. Data were collected through observation, questionnaires, and in-depth interviews, then analyzed using descriptive and inferential statistics (t-tests) followed by qualitative thematic analysis. The findings reveal that the integrated IBL-LSTEAM-SEL approach effectively improves children's planning, problem-solving, and self-control skills. The study concludes that this learning model supports deep learning and promotes holistic child development. The implication of the study emphasizes the need for continuous teacher training in implementing integrated pedagogical approaches to improve the quality of early childhood education.